Algoritmo de escalonamento DRR com quantum adaptativo para o tráfego downlink de redes IEEE 802.16j - Santos, Einar César (2012)
IEEE 802.16j networks provide, through the Relay Station (RS), improvements with regard to previous specifications of WiMAX in terms of increased coverage area, reduction of deployment costs due to low cost of RS compared to a Base Station (BS) and system average throughput increase. Its main purpose is to meet demands for wireless broadband access at lower cost. The efficient resource allocation is a challenge in the IEEE 802.16 standard and requires total commitment of scheduling algorithm. Few proposals for downlink scheduling developed for IEEE 802.16j networks are relevant to the present moment, and much of it disregards the maximum utilization of basic resources available, such as using only one RS due to a large traffic load, for example. In view of this, we propose the application of a Deficit Round Robin (DRR) algorithm with adaptive quantum operating together with a queue management and congestion control in RS. In the proposed DRR scheduling, implemented in the BS downlink scheduler, the quantum is calculated using the Maximum Transmission Unit (MTU) size and information about the congestion state in RS. In order to balance the average queue length in the output buffer of RS, we have implemented an algorithm based on Adaptive Random Early Detection (ARED). Finally, the proposed solution was evaluated using modeling and simulation. The simulation results demonstrate good performance of the proposed classes for UGS, rtPS, nrtPS and BE compared to a conventional DRR scheduling without queue management.